Peningkatan Uji Kuat Tekan Paving Block Dengan Bahan Limbah - Andy Eka Saputra (Jurusan Teknologi Pertanian, 2019)
The research will be carried out at the Soil and Water Engineering Laboratory and the Lampung State Polytechnic Agricultural Mechanization Laboratory for 6 months. In the results of each manufacture of Paving blocks for each sample, the compressive strength value is quite stable and continues to increase starting from day 1 to 28. Cement as a binding material succeeded in binding fly ash and bottom ash perfectly due to the fly ash and bottom ash content reaching optimum laboratory standard density with dry content weight of 1.47 gr/cm3 with the addition of 3000cc water at a ratio of 1: 4 making a determinant of the strength of the paving block by achieving average maximum strength of 192 kg/cm2 or K 190 and 214 kg / cm2 or K 200 at 28 days old, and included in the class B katogari SNI 03 -0691-1996, with these results showing a high increase in class D quality in research previously increased to quality B with SNI standards.Â Keywords: paving blocks, fly ash, bottom as.,